2008
DOI: 10.1177/0267659109104561
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cognitive test performance in patients undergoing primary CABG and other CPB-assisted cardiac procedures

Abstract: Cardiac surgical procedures assisted by cardiopulmonary bypass (CPB) impair cognitive functions. Several studies, however, showed that cognitive functions were unaffected in patients undergoing either primary coronary artery bypass grafting (CABG) or more complex surgery assisted by CPB. Therefore, we conducted a straightforward study to compare patient groups who differed significantly in terms of risk factors such as prolonged CPB times. Consecutive patients (n = 54) were included, undergoing either non-prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Level of schooling and cognition were also expressed in different ways. A number of authors did not report the educational level of the population studied 9 , 16 , 18 , 24 , 32 , 33 , 37 while the majority expressed schooling as mean years of education 6 , 10 , 13 , 15 , 20 , 27 , 28 , 30 , 36 giving an overall mean of 11.5 years and range of 14.1-4.2 years, with the latter lower figure attributed to the study conducted in Brazil. Among the studies opting to express schooling by category, a wide variety of classifications was observed.…”
Section: Resultsmentioning
confidence: 97%
“…Level of schooling and cognition were also expressed in different ways. A number of authors did not report the educational level of the population studied 9 , 16 , 18 , 24 , 32 , 33 , 37 while the majority expressed schooling as mean years of education 6 , 10 , 13 , 15 , 20 , 27 , 28 , 30 , 36 giving an overall mean of 11.5 years and range of 14.1-4.2 years, with the latter lower figure attributed to the study conducted in Brazil. Among the studies opting to express schooling by category, a wide variety of classifications was observed.…”
Section: Resultsmentioning
confidence: 97%
“…The negative impact of diabetes on vein grafts may be circumvented in part by the use of arterial grafts whenever feasible. Morbidity associated with CABG can be considerable [106][107][108][109][110] and may include at least transitory postoperative cognitive impairment. Nevertheless, just as is the case with PCI, advances in surgical techniques have led to improvement in outcomes after CABG.…”
Section: Management Of Hyperglycemia After Cabg or Pci In Patients Wimentioning
confidence: 99%
“…One is the possible impairment of cognitive function after CABG [62]. This issue is complex, however, in view of an improvement after an initial decline in cognitive function over time after CABG [62].…”
Section: Revascularization In Patients With An Acsmentioning
confidence: 99%
“…One is the possible impairment of cognitive function after CABG [62]. This issue is complex, however, in view of an improvement after an initial decline in cognitive function over time after CABG [62]. Furthermore, it is possible that the rate and magnitude of decline in cognition may not differ in patients with CAD who have not undergone CABG [63].…”
Section: Revascularization In Patients With An Acsmentioning
confidence: 99%